The Role of the Goverment’s Internal Control System as An Intervening Variable on the Influence of Non-Compliance with The Quality of Local Government Financial Statements In Indonesia - Nur Hidayati, Aris Eddy Sarw Sunarti & Dewi Saptantinah P A (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aims to examine the influence of the goverment’s internal controlsystem and non-compliance with regulations on the quality of local govermentfinancial statements. Local goverments financial reports have a function as a formof accountability from the goverment to the public. This study uses Secondary datawith local goverments financial statements as Indonesia amounted to 259 from2010 to 2014 using eviews9 test tool. The result showed that the govermentsinternal control system and regulatory non-compliance have a significant effect onthe quality of local goverment financial statements with the results on internalgoverment control system variables of -0.932243 and the variable non-complianceregulation amounted to 0.830193 which means both variables above the significantvalue 0,05. On the internal goverment control system variables and regulatory noncomplianceaffecting 0,203449 which means 0,796 influenced by other variables.Keywords : quality of financial statements, goverment internal control system, non-complianceregulation